Smart Digital Attack As an Acceleration Drive of Firm Value Creation in Digital Era - Rahmawantari, Dhistianti Mei; Purwoko, Bambang; Suratno, Suratno (Samudra Publisher, 2026)
This study aims to examine and investigate the determinants of firm value creation in this digital era, focused on the role of financial literation as a moderating variable. As the shifting of outside investor perspectives occurred on which key elements can drive accelerated firm value creation in this digital era, business leader should objectively appraise their potential strengths and weaknesses aspect to maximize value creation within their company, so its risk profile will reducing as well. This research resulted a concept called